PERBEDAAN EFEKTIVITAS PELATIHAN BURPEE EXERCISE DENGAN PELATIHAN HEXAGON DRILL DALAM MENINGKATKAN KELINCAHAN PADA ATLET SEPAKBOLA ANAK USIA 9 – 11 TAHUN DI SEKOLAH SEPAKBOLA GUNTUR, DENPASAR - Ida Ayu Eka Pradnya Paramita Dewi Paramita Dewi; Anak Ayu Nyoman Trisna Narta Dewi; I Gusti Ayu Artini (Majalah Ilmiah Fisioterapi Indonesia, 2017)
ABSTRACT Agility is one's ability to change position and direction of motion quickly, efficiently and precisely without losing balance. Agility is very important in football. Based on the theory that burpee's exercise and hexagon drill can improve agility. This study was conducted to compare burpee's exercise and hexagon drill in improving agility in soccer athletes of children aged 9-11 years in Football School Guntur Denpasar. Hypothesis Test with Paired Sample T-test and Independent Sample T-test. The result of Paired Sample T-test in Burpee’s Exercise group is p=0.001 (p<0.05) and Hexagon Drill group is p=0.000 (p<0.05) showed the significant differences in the agility improvement before and after intervention. The result of Independent T-test showed there was significant differences between Burpee’s Exercise and Hexagon Drill, where p=0.046 (p<0.05). This it can be concluded that Burpee’s Exercise is better for improving agility than Hexagon Drill of soccer athletes of children aged 9-11 years at the Football School Guntur Denpasar. Keywords: Agility, Burpee's exercise, Hexagon drill.